The Effects of Arterial Hypertension and Age on the Sublingual Microcirculation of Healthy Volunteers and Outpatients with Cardiovascular Risk Factors. (August 2015) - Kanoore Edul, Vanina S.; Ince, Can; Estenssoro, Elisa; Ferrara, Gonzalo; Arzani, Yanina; Salvatori, Carolina; Dubin, Arnaldo
Abstract Objectives To quantitatively assess the effects of age, blood pressure, chronic arterial hypertension, and physical activity on sublingual microcirculation in ambulatory volunteers. Methods Sublingual microcirculation was assessed in 61 volunteers with or without chronic arterial hypertension. Results Volunteers with chronic arterial hypertension had lower TVDall vessels, and TVDsmall vessels and PVDsmall vessels than those without this condition (16.0 ± 1.4 vs. 17.2 ± 1.6 mm/mm2, p < 0.01, 15.1 ± 1.3 vs. 16.1 ± 1.7 mm/mm2, p < 0.04, and 15.1 ± 1.3 vs. 16.1 ± 1.7 mm/mm2, p < 0.04, respectively). Mean blood pressure correlated with TVDall vessels (r = −0.34, p < 0.01), TVDsmall vessels (r = −0.31, p < 0.02), and PVDsmall vessels (r = −0.27, p < 0.04) but not with other microvascular variables. Age was not correlated with any microcirculatory variables. Physical activity correlated with TVDall vessels and RBCVsmall vessels (r = 0.30, p < 0.02 and r = −0.47, p < 0.001, respectively). Chronic arterial hypertension was the only independent determinant of PVDsmall vessels. Conclusions Preexistent chronic arterial hypertension was associated with lower vascular densities. In contrast, age showed no effect on sublingual microcirculation.